Do Managers Pursue Their Budget Goals Using Revenues or Expenses? - Jackson, Scott B.; Salzsieder, Leigh; Schaefer, Tammie J. (The Accounting Review, 2025)
ABSTRACT Evidence reveals that managers exercise discretion over budget estimates, but little is known about whether revenues or expenses are more susceptible to budget discretion. Drawing upon regulatory focus theory, we predict a pattern of budget discretion that has not previously been identified. To test our theory, we conduct a series of experiments where managers face a goal to either minimize the performance metric to avoid missing the target (minimal budget goal) or maximize the performance metric to achieve a desired outcome (maximal budget goal). When managers face a minimal budget goal, they are more likely to make self-interested budget estimates for uncertain expenses than monetarily equivalent uncertain revenues. Conversely, when managers face a maximal budget goal, they are more likely to make self-interested budget estimates for uncertain revenues than monetarily equivalent uncertain expenses. Thus, managers prefer acts of inclusion over acts of exclusion when pursuing their budget goals. JEL Classifications: G31, M10, M40.